Soul Shaking as Reason for Criminal Abolition: The Dilemma Between Legal Certainty and Justice/Keguncangan Jiwa Sebagai Alasan Penghapus Pidana: Dilema Antara Kepastian Hukum dan Keadilan - Gumelar, Krishna (Fakultas Syariah, 2021)
Abstract: The forced defense that goes beyond the limits (Noodweer Exces) is still interesting to study. Criminal law experts still debate criteria for a mental shock that cause excessive defense. This study aims to describe the criteria for acts that can be referred to as noodweer exces in criminal cases and analyze the meaning of mental shock in noodweer exces so that there are no multiple interpretations. This article is the result of doctrinal legal research with a statutory approach. The results of this study indicate that a person's behavior is called a noodweer exces if it begins with an immediate attack that is against the law and the victim feels the need to defend himself. The grammatical interpretation of Article 49 of the Criminal Code shows that feelings of discomfort, anger, confusion, and fear that result in great mental shock in a person can be a reason for someone to carry out an excessive forced defense. However, severe mental agitation must get information from a psychologist.Keywords: noodweer exces; shock of the soul; criminal offenses.Abstrak: Pembelaan terpaksa (Noodweer Exces) akibat kegoncangan jiwa masih menarik untuk dilakukan kajian. Kriteria keguncangan jiwa yang menyebabkan pembelaan berlebihan masih diperbedatkan oleh para pakar hukum pidana. Penelitian ini bertujuan untuk mendeskripsikan kriteria perbuatan yang dapat disebut sebagai noodweer dalam perkara tindak pidana dan menganalisis terkait makna keguncangan jiwa dalam noodweer exces sehingga tidak terjadinya multitafsir. Artikel ini adalah hasil penelitian hukum doktrinal dengan pendekatan perundang-undangan. Hasil kajian ini menunjukkan bahwa perilaku seseorang disebut sebagai noodweer jika diawali dengan serangan seketika yang bersifat melanggar hukum dan korban merasa perlu melakukan pembelaan. Penafsiran gramatikal terhadap Pasal 49 KUHP menunjukkan bahwa perasaan tidak nyaman, amarah, bingung, dan ketakutan sehingga berakibat pada kegoncangan jiwa yang hebat pada diri seseorang dapat menjadi sebab pembenar seseorang melakukan pembelaan terpaksa secara berlebihan. Meskipun demikian, kegoncangan jiwa yang hebat harus mendapat keterangan dari psikolog.